Structural evolution of the Ongul Islands, Lutzow-Holm Complex, East Antarctica - Kawakami,Tetsuo; Ikeda,Takeshi (National Institute of Polar Research, 2004)
P(論文) We describe outcrop-scale folds at ten localities in the Ongul Islands, including five localities where interference patterns of more than two stages of folding are observed, along with structural data summarized in stereogram. F_(m-1) are recognized as isoclinal to rootless folds with fold axes trending NNW-SSE. S_(m-1) is defined by orthopyroxene, hornblende and biotite aligned parallel to the compositional layering and as axial planar foliation in F_(m-1) folds, and is folded by tight F_m. F_m have axial traces that trend NNW-SSE and subvertical axial planes dipping ENE and striking NNW-SSE. Axial planar foliation S_m is defined by biotite and hornblende in the hinges of F_m. F_(m-1) axes typically trend parallel to F_m axes and can be discriminated only in areas showing interference patterns. F_(m+1) are gentle to open with axes trending approximately N-S. Boudinage formed before Dm and interboudin partitions are filled with orthopyroxene-bearing leucosome. Judging from minerals constituting D_(m-1) and D_m structures, D_(m-1) occurred under granulite-facies conditions and at least part of D_m probably under amphibolite-facies conditions. departmental bulletin paper